KECENDERUNGAN KEPUASAN KERJA SEBAGAI TRIGGER TURNOVER KARYAWAN - Saputra, Raditya Adi (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
The purpose of this study are: (1) To determine the effect of work stress, compensation, organizational climate on job satisfaction; (2) To determine the effect of job satisfaction, work stress, compensation, and organizational climate on turnover intention. The population in this study are employees of the Cooperative KOKAPURA AVIA totaling 180 people, while employees who have worked more than three years as many as 128 people. Samples were taken 97 people. The technique of collecting data using questionnaires. The analysis used is multiple regression analysis and path analysis using PLS 3.0 Smart program. Based on the results of the study concluded that: (1) Work stress, compensation incentive, organizational climate  significantly influence towards employee job satisfaction; (2) Job satisfaction, work stress, compensation, and organizational climate significantly influence toward employee turnover intention Keywords: work stress, incentive compensation, organizational climate, job satisfaction, turnover intention